The variations of temperature, pressure and wind speed values: Effects on gravity waves - Can, Z; Aslan, Z; Oguz, O (EDITRICE COMPOSITORI BOLOGNA, 2002)
According to the theoretical studies, gravity waves, which are excited in the lower atmosphere, can transport momentum and energy on to the upper levels. Gravity waves are attenuated by interacting with the large-scale wind motions in the upper part of the middle atmosphere. Different meteorological parameters and atmospheric circulations are known as one of the sources of excitement of gravity waves. The main purpose of this paper is to analyze the onset of some gravity waves (GWs), and seasonal variations of gravity waves over Istanbul. Radiosonda data of Istanbul in troposphere and lower stratosphere (1000 hPa-30 hPa) between 1993 and 1997 is analyzed. Daily, monthly and annual variation of pressure heights, air temperature, horizontal wind speed and deviations, from mean values are interpreted. Zonal and meridional wind speed variations show the effects of gravity waves for different pressure levels in the troposphere. These waves lead the meso-scale waveform structures in spring, autumn and winter.
Keywords: CYCLE